The Effect of Interpersonal Skills and Technical Skills on The Effectiveness of Audit Report Survey at PT. Bank Neo Commerce Indonesia - Asyari; Achyarsyah, Padri; Suryanti, Heny; Hidayatullah, Deni (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2025)
This research aims to analyze the influence of interpersonal skills and technical skills on the effectiveness of financial report audits at PT. Neocommerce Bank in Jakarta. Methodology This research uses a quantitative descriptive approach because researchers use survey data collection methods and direct interviews with the PT company. Neocommerce Bank. This research is classified as quantitative descriptive research, namely testing the relationship between the influence of interpersonal skill and technical skill variables on the effectiveness of financial report audits. The research sample was conducted for the internal audit of the company PT. Jakarta Neocommerce Bank. With a sample size of 58 employees. The research hypothesis was processed with the help of SPSS 25 software. The research results show that interpersonal skills have a significant effect on the effectiveness of financial report audits. Technical skills have a significant positive effect on the effectiveness of financial report audits. The R Square Test results show that the variables are able to contribute to the effectiveness of financial report audits at Bank Neocommerce